A Signs and Meanings of Pamali Utterances in The Religiosity of Kampung Naga Indigenous Communities: A Semiotic Theory Perspective: A Semiotic Theory Perspective - Widiawati, Nani; Nor, Mohd Roslan Mohd; Restiani (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
This research is motivated by differences in people's beliefs regarding the Pamali (taboo) tradition, which is considered by some groups to represent wisdom, but by as a type of superstition that must be avoided. This results in the Pamali tradition beginning to be marginalised from modern life. However, in the Kampung Naga, one of the villages in Indonesia , the tradition is still maintained in the practice of religion and modernisation. The paper aims to analyse Pamali utterances based on the perspective of semiotic theory and their relationship with the religiosity of the Kampung Naga indigenous community. The qualitative research uses an phenomenological design that applies linguistic theory as an analytical tool. It was found that according to the theory of meaning, Pamali utterances are based on the relevance of the relationship between sign, referent, and interpretant. Pamali is interpreted as taboo by society, and therefore people do not violate it. The content of the message in Pamali utterances is in harmony with the content of the Islamic message, so the reflection is a crystallisation of the religious teachings adhered to by the village people.